The Effect of Audit Opinion and Auditor Turnover on Audit Delay with KAP Reputation as Quasi Moderator - Marini Lestari; Yulis Diana Alfia (E-Jurnal Akuntansi, 2025)
This study aims to examine the effect of audit opinion and auditor turnover on audit delay, with the reputation of Public Accounting Firms (KAP) as a moderating variable. The research focuses on non-primary consumption sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A total of 356 observations were selected using purposive sampling. Data analysis was performed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that audit opinion, auditor turnover, and KAP reputation have a positive effect on audit delay. However, KAP reputation does not moderate the relationship between either audit opinion or auditor turnover and audit delay. These findings imply that while KAP reputation directly influences audit timeliness, it does not function effectively as a moderating factor.